2020
DOI: 10.3390/ijms21144925
|View full text |Cite
|
Sign up to set email alerts
|

Beyond What Your Retina Can See: Similarities of Retinoblastoma Function between Plants and Animals, from Developmental Processes to Epigenetic Regulation

Abstract: The Retinoblastoma protein (pRb) is a key cell cycle regulator conserved in a wide variety of organisms. Experimental analysis of pRb’s functions in animals and plants has revealed that this protein participates in cell proliferation and differentiation processes. In addition, pRb in animals and its orthologs in plants (RBR), are part of highly conserved protein complexes which suggest the possibility that analogies exist not only between functions carried out by pRb orthologs themselves, but also in the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 288 publications
(403 reference statements)
0
15
0
Order By: Relevance
“…The LECA cell cycle network also likely included at least one CDK and multiple cyclins that regulated events in different phases of the cell cycle ( Figure 1 B). Studies from a variety of eukaryotes have demonstrated how RB and E2F homologs link the activity of CDKs with the periodic expression of genes important for cell cycle progression and cell division [ 13 , 17 , 27 ]. Phosphorylation of RB by D-type cyclin-CDKs initially allows the induction of genes important for the G1/S phase transition, including G1/S phase cyclins, like human CCNE (cyclin E) and CCNA (cyclin A).…”
Section: Evolutionary History Of E2f and Rb Homologs In Eukaryotesmentioning
confidence: 99%
See 4 more Smart Citations
“…The LECA cell cycle network also likely included at least one CDK and multiple cyclins that regulated events in different phases of the cell cycle ( Figure 1 B). Studies from a variety of eukaryotes have demonstrated how RB and E2F homologs link the activity of CDKs with the periodic expression of genes important for cell cycle progression and cell division [ 13 , 17 , 27 ]. Phosphorylation of RB by D-type cyclin-CDKs initially allows the induction of genes important for the G1/S phase transition, including G1/S phase cyclins, like human CCNE (cyclin E) and CCNA (cyclin A).…”
Section: Evolutionary History Of E2f and Rb Homologs In Eukaryotesmentioning
confidence: 99%
“…RB homologs in animals and plants actively repress transcription by interacting with and recruiting chromatin modifying enzymes to the promoters of E2F target genes [ 13 , 17 , 27 , 35 , 36 ]. Several of these chromatin modifying enzymes contain a LxCxE amino acid motif that binds to a conserved cleft in the RB pocket domain and allows RB to bind both the chromatin modifiers and E2F factors simultaneously [ 37 ].…”
Section: Evolutionary History Of E2f and Rb Homologs In Eukaryotesmentioning
confidence: 99%
See 3 more Smart Citations